The Economic Stretch of the Entertainment Stage: The Role of Fair and Development Promotion in the Promotion of Industry and Small Business in Central Java 1981-1995 - Al Dzaky, Muhammad Lutfi; Wibowo, Eka Yudha (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Central Java Fair and Development Promotion (Pekan Raya dan Promosi Pembangunan) began in 1970 under the name Pekan Raya Semarang. This research examines the transformation of Central Java Fair and Development Promotion as a strategic policy instrument during the formative period 1981-1995. Against the backdrop of Central Java's important position in national development, this research focuses on two main issues, namely the rationale behind the organization of Fair and Development Promotion and its significant role in the development of the Fair and Development Promotion and its significant role for the development of industry and small businesses in the province. and small businesses in the province. This research uses the historical method, with the heuristic stage relying on primary sources in the form of archival newspapers from 1981-1995, followed by source criticism, interpretation, and historiography. The results show that Pekan Raya dan Promosi Pembangunan was organized with the aim of as a media for development promotion, accelerator of domestic product marketing, a driver of non-oil and gas exports, and a vehicle for empowering small entrepreneurs. It was concluded that Pekan Raya dan Promosi Pembangunan successfully evolved from an annual exhibition into a vital and effective promotional institution in a vital and effective promotional institution in accelerating regional economic growth, especially in strengthening and empowering small entrepreneurs. regional economic growth, especially in strengthening and empowering the small and medium business sector.